(3OjhGf GdSQj GdQaGAs - (3GdnqSpQqj Hf CMeO Hf GdSQj GdcfOj, CHh GdMSf GdnqQnqaGA,J (B366 (3g` s
(3ChdgG (B:s
(3bGd GdSQj jeOM CHGdYdGA gH Hf gGQhf, hjYQV aj bUjOJg HGdNGdOjf(B: (3TZa GdMjG Hc ef QHG hedGYH de JNd ef TZa hOeY SGcH s
(3BNQgG (B:s
(3CKQjJ EP LGhRJ QHYc fGRdG acCffj LGQ GdQHjY GdfGRd s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B208s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B117 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B792s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(3098) s
Keywords: (3GdCOHs